Changes in hippocampal volume, synaptic plasticity and amylin sensitivity in an animal model of type 2 diabetes are associated with increased vulnerability to amyloid-beta in advancing age - Tarhan, Melih; Hartl, Tim; Shchyglo, Olena; Colitti-Klausnitzer, Jens; Kuhla, Angela; Breuer, Tobias Maximilian; Manahan-Vaughan, Denise (Frontiers in Aging Neuroscience, 2024)
Type-2 diabetes (T2D) is a metabolic disorder that is considered a risk factor for Alzheimer's disease (AD). Cognitive impairment can arise due to hypoglycemia associated with T2D, and hyperamylinemia associated with insulin resistance can enhance AD pathology. We explored whether changes occur in the hippocampus in aging (6–12 months old) female V-Lep○b-/- transgenic (tg) mice, comprising an animal model of T2D. We also investigated whether an increase in vulnerability to Aβ (1–42), a known pathological hallmark of AD, is evident. Using magnetic resonance imaging we detected significant decreases in hippocampal brain volume in female tg-mice compared to wild-type (wt) littermates. Long-term potentiation (LTP) was impaired in tg compared to wt mice. Treatment of the hippocampus with Aβ (1–42) elicited a stronger debilitation of LTP in tg compared to wt mice. Treatment with an amylin antagonist (AC187) significantly enhanced LTP in wt and tg mice, and rescued LTP in Aβ (1–42)-treated tg mice. Taken together our data indicate that a T2D-like state results in an increased vulnerability of the hippocampus to the debilitating effects of Aβ (1–42) and that effects are mediated in part by changes in amylin receptor signaling.